2008
DOI: 10.1111/j.1749-4486.2008.01674.x
|View full text |Cite
|
Sign up to set email alerts
|

Superficial temporal vein graft in stapedotomy: a functional and aesthetic alternative

Abstract: The Causse technique of performing stapedotomy with vein graft interposition is widely-employed, with the vein graft harvested from the dorsum of the hand/wrist. Donor site scarring may be of cosmetic concern, especially in female patients. A prospective series of 19 patients undergoing stapedotomy with vein graft harvested from the superficial temporal vein is evaluated from aesthetic and functional perspectives. Results show that vein interposition from this donor site is not only aesthically acceptable but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…A long-term prospective audiometric evaluation study by Vincent et al, [ 36 ] demonstrated the stability of the results with vein graft over time. The vein is traditionally harvested from the wrist or dorsum of the hand; alternatively, the superficial temporal vein or its branches can be used, with the added advantages of better cosmetic outcome and working on the same operative site [ 37 ]. Like the superficial temporal vein, the tragal or conchal perichondrium has the advantage to be accessible in the same operative field, although there is some concern for the chondrogenic potential of this graft, which can probably be avoided by orienting it properly and not traumatizing it [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A long-term prospective audiometric evaluation study by Vincent et al, [ 36 ] demonstrated the stability of the results with vein graft over time. The vein is traditionally harvested from the wrist or dorsum of the hand; alternatively, the superficial temporal vein or its branches can be used, with the added advantages of better cosmetic outcome and working on the same operative site [ 37 ]. Like the superficial temporal vein, the tragal or conchal perichondrium has the advantage to be accessible in the same operative field, although there is some concern for the chondrogenic potential of this graft, which can probably be avoided by orienting it properly and not traumatizing it [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In those papers that reported the ABG closure correctly, only 11.8 per cent reported the mean, SD and range of their results 6 , 19 , 22 , 29 , 42 , 44 , 51 . A one-year follow-up audiogram was conducted in only 60.1 per cent of studies 7 , 14 16 , 19 , 21 , 23 , 25 , 27 , 29 31 , 33 , 36 39 , 41 – 45 , 47 , 50 , 51 , 55 , 57 , 59 – 61 Non-adherence to current guidelines can lead to over-inflated reports of successful air–bone gap closureThis can affect the consent process and patient expectationsClear guidelines exist for reporting otological surgery outcomesNevertheless, incorrect reporting continues and minimal datasets are still missingAdherence to guidelines provides accurate outcomes and inter-study comparisons…”
Section: Discussionmentioning
confidence: 99%
“…The tympanomeatal flap was finally repositioned after performing the bend and lift test. 12,13
Figure 2.(a) Vein graft surround diagram showing the piston placed in the oval window (OW) fenestra surrounded by vein graft. (b) Microscopic image of vein graft surround technique.
…”
Section: Methodsmentioning
confidence: 99%
“…The tympanomeatal flap was finally repositioned after performing the bend and lift test. 12,13 Audiological assessment Air-bone gap (ABG), air conduction and bone conduction thresholds were measured pre-operatively and postoperatively. A 4-frequency pure tone average value was calculated for air conduction and bone conduction thresholds at 500, 1000, 2000 and 4000 Hz obtained pre-and postoperatively.…”
Section: Methodsmentioning
confidence: 99%